2001
DOI: 10.1038/sj.cgt.7700408
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific expression of a suicide gene for selective killing of neuroblastoma cells using a promoter region of the NCX gene

Abstract: The human NCX gene, a homologue of the murine neural crest homeobox ( Ncx / Hox11L.1 ) gene whose expression is restricted to a subset of neural crest -derived tissues, was expressed in human neuroblastoma cells but not in other tumors or fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…INSM1 expression peaks in early fetal development and is absent from normal adult tissues. Although INSM1 is silenced in normal adult tissues, it is highly reactivated in tumors of neuroendocrine origin, which display an ideal expression pattern for use in transcriptionally targeted cancer gene therapy (Narita et al, 2001;Adachi et al, 2002;Steffens et al, 2004;Arvidsson et al, 2005). Using a 1.7-kb (bp À1661 to þ 40) INSM1 promoter-driven LacZ transgenic mouse line, we convincingly demonstrated that the information required for tissue-specific expression of the INSM1 gene is present in the 5 0 -upstream regulatory region (Breslin et al, 2003).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…INSM1 expression peaks in early fetal development and is absent from normal adult tissues. Although INSM1 is silenced in normal adult tissues, it is highly reactivated in tumors of neuroendocrine origin, which display an ideal expression pattern for use in transcriptionally targeted cancer gene therapy (Narita et al, 2001;Adachi et al, 2002;Steffens et al, 2004;Arvidsson et al, 2005). Using a 1.7-kb (bp À1661 to þ 40) INSM1 promoter-driven LacZ transgenic mouse line, we convincingly demonstrated that the information required for tissue-specific expression of the INSM1 gene is present in the 5 0 -upstream regulatory region (Breslin et al, 2003).…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, alternative treatment options for these forms of cancer are needed. Gene therapy approaches focused toward high-risk neuroblastoma and central nervous system tumors such as medulloblastoma have used common neuronal-specific promoters from the genes encoding midkine, tyrosine hydroxylase, neural crest homeobox (NCX), and Mash1 (Narita et al, 2001;Adachi et al, 2002;Steffens et al, 2004;Arvidsson et al, 2005). Despite promising results from these gene therapy strategies, one significant barrier is the continuous expression of these gene products, with the exception of Mash1, in normal adult neuronal cells.…”
mentioning
confidence: 99%
“…10,28 Because of this feature, the brain will be protected from the NT-polyplex-mediated transfection of cell-death-promoting genes. In addition, NTSR1-bearing cells of healthy peripheral tissues can be protected from the deleterious effects of transgene expression using a neuroblastoma cell-specific promoter such as the NCX promoter 36 or a tumor-selective promoter such as the E2F-1 promoter to confine the therapeutic effect within the tumoral cells. 37 In this work, we used the HSVTK-GCV system because of its efficiency to cause cell death in addition to the bystander effect.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide gene therapy with the herpes simplex virus thymidine kinase (HSV-TK) fragment, the most widely used strategy for the cancer therapeutic study [3] , has been shown to exert antitumor efficacy in various cancer models [4][5][6][7] . However, its efficacy seems not to be fully developed to eliminate tumor cells in some of the investigations [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%